A rare case of leiomyoma of uterus with cystic degeneration - Panda, Soumya Ranjan; Chandra, Charu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Leiomyoma of the uterus is the most common tumor of the female pelvis. The size of leiomyomas varies from microscopic to giant. Giant myomas are exceedingly rare. Here, we present a case of a woman with uterine myoma that had undergone cystic degenerative changes, mimicking an ovarian malignancy. It provided a lot of diagnostic challenge as even ultrasonography and CT scan were not confirmatory. Finally laparotomy was done keeping everything ready for the management ovarian malignancy. On laparotomy the mass was found to be leiomyoma of uterus with cystic degeneration.